1983
DOI: 10.1007/bf00777469
|View full text |Cite
|
Sign up to set email alerts
|

Genetic interpretation of polytene chromosomes banding pattern

Abstract: This mini-review covers new data regarding the problem of the functional organization of polytene chromosomes: The localization of RNA synthesis in the polytene chromosome puffs, diffuse bands and interbands; The relative stability of banding pattern and its functional value; The informational content of bands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…As in the hsp60 F409 flies, hsp60 G93 homozygous mutant animals die early in embryogenesis [15], embryos are amorphous and their nuclei are distributed randomly (data not shown). The hsp60 G93 sequence did not show any change in the ORF.…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…As in the hsp60 F409 flies, hsp60 G93 homozygous mutant animals die early in embryogenesis [15], embryos are amorphous and their nuclei are distributed randomly (data not shown). The hsp60 G93 sequence did not show any change in the ORF.…”
Section: Resultsmentioning
confidence: 72%
“…The wild‐type stock was OreR. The hsp60 F409 and hsp60 G93 alleles were maintained in the presence of the FM6 balancer [15,16]. Flies were reared on standard yeast dextrose medium at 25°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The chromosomes of multicellular animals have a regular and inheritable physical organization. This was first recognized in studies on the lampbrush chromosomes in amphibian oocytes and the polytene chromosomes of insects (Callan, 1963;Nora et al, 2020;Zhimulev and Belyaeva, 1991;Zhimulev et al, 1983). Subsequent research has shown that the architectural features inferred from analysis of lampbrush and polytene chromosomes are present in chromosomes throughout much of the animal kingdom.…”
Section: Introductionmentioning
confidence: 93%
“…Results from in situ hybridization to polytene chromosomes of a clone spanning the breakpoint site suggested that the break lies more proximally, most probably in the very thin bands around 9E6, which is more in line with the original localization in 9 E 7.8 (ref. 38). This observation is further confirmed by the fact that the above clone was obtained from a chromosomal walk extending proximally from an entry point at 9E3.4.…”
mentioning
confidence: 93%